PEMAHAMAN KEWAJIBAN SUAMI TERHADAP ISTRI MENURUT HUKUM POSITIF (STUDI KASUS DI STM SERIKAT AMAL RIDHO DESA BANDAR KLIPPA) - Yeltriana, Ismed Batubara, Alkausar Saragih (NERACA KEADILAN, 2024)
This research aims to determine the understanding of husbands at the STM Amal Ridho Union of Bandar Klippa Village regarding the husband's obligations towards his wife according to positive law. This research uses qualitative research methods with data collection techniques in the form of in-depth interviews, observation and documentation. Based on the research results, it was concluded that the understanding of husbands at the Bandar Klippa Village Charity Union STM regarding the husband's obligations towards his wife according to positive law was quite good. Most husbands understand that a husband's obligations towards his wife include physical support, mental support and protection. However, there are still some husbands who do not fully understand the husband's obligations towards his wife according to positive law. This is caused by several factors, namely the husband's lack of understanding of positive law, lack of communication between husband and wife, and lack of socialization from the government. Based on the research results, it is recommended that the government conduct outreach regarding the obligations of husbands towards wives according to positive law to the community, especially to husbands. Apart from that, husbands and wives also need to improve their communication and understanding of their respective obligations in marriage. The understanding of husbands at the Bandar Klippa Village Charity Union STM regarding the husband's obligations towards his wife according to positive law is quite good. However, there are still some husbands who do not fully understand the husband's obligations towards his wife according to positive law. This is caused by several factors, namely the husband's lack of understanding about positive law, lack of communication between husband and wife, and lack of socialization from the government. Based on the research results, it is recommended that the government conduct outreach regarding the obligations of husbands towards wives according to positive law to the community, especially to husbands. Apart from that, husbands and wives also need to improve their communication and understanding of their respective obligations in marriage.